(untitled) (Global Journal of Medical Research, 2023)
Every person’s health is impacted by a confirmation of circumstances, and certain diseases are fatal and have serious side effects. One such serious condition that affects people of all ages is heart disease. this paper suggests a preprocessing strategy to improve the categorization precision of ECG data We are suggesting an ECG sensor-based healthcare monitoring system. Since the values are so crucial, ECG sensors are necessary for patient remote monitoring. Elements from the ECG wave are extracted using a verification of extraction techniques to be able to accurately predict cardiac disease The patient’s ECG is continuously monitored using a mobile app. The different algorithms used in data mining eliminate the extra time and work required to perform multiple tests to identify diseases. Data collection employs ECG sensors. The acquired data is stored on a storage device before data Mining techniques are used to it. These equations indicate the patient’s potential for cardiac disease. Doctors may utilise the outcomes for diagnostic purposes. The technology will predict cardiac illness by utilizing machine learning methods.